Analisis Pengelolaan Keuangan Sekolah Di Yayasan Madrasah Aliyah Darul Qalam - Deni Saputra; Rizky Hariadi; Asnaini Asnaini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research was conducted with the aim of understanding how to use the principles of openness and responsibility in the field of school finances at Madrasah Aliyah Darul Qalam. How to research using one type of research, namely the type of field research (field research) using a qualitative descriptive approach. This study found that the application of the principles of openness and responsibility at the Darul Qalam Madrasah Aliyah Foundation has gone quite well, that is, there is interference from all the school environment, starting from the committee, treasurer, teachers and others. The fact is that all implementation of financial reports is open and in accordance with applicable regulations. Keywords: Transparency, Accountability, Management School Finance